Booms, Busts, and Common Risk Exposures - KOPYTOV, ALEXANDR (Journal of Finance, 2023)
ABSTRACT I present a dynamic general equilibrium model in which commonality in bank assets endogenously changes over the business cycle and shapes systemic risk. To reduce individual risks, banks diversify, increasing portfolio overlap and hence the similarity of their exposures to fundamental shocks. Systemic financial crises burst at the end of credit booms when productive investment opportunities are exhausted, banks' diversification incentives are strong, and their portfolios are highly correlated. A calibrated model is able to match key moments related to frequency, severity, and the economy's behavior around systemic crises.